Improving Adolescent Sexual and Reproductive Health: A Systematic Review of Potential Interventions - Salam, Rehana A.; Faqqah, Anadil; Sajjad, Nida; Lassi, Zohra S.; Das, Jai K.; Kaufman, Miriam; Bhutta, Zulfiqar A. (Journal of adolescent health, 2016)
Adolescents have special sexual and reproductive health needs (whether or not they are sexually active or married). This review assesses the impact of interventions to improve adolescent sexual and reproductive health (including the interventions to prevent female genital mutilation/cutting [FGM/C]) and to prevent intimate violence. Our review findings suggest that sexual and reproductive health education, counseling, and contraceptive provision are effective in increasing sexual knowledge, contraceptive use, and decreasing adolescent pregnancy. Among interventions to prevent FGM/C, community mobilization and female empowerment strategies have the potential to raise awareness of the adverse health consequences of FGM/C and reduce its prevalence; however, there is a need to conduct methodologically rigorous intervention evaluations. There was limited and inconclusive evidence for the effectiveness of interventions to prevent intimate partner violence. Further studies with rigorous designs, longer term follow-up, and standardized and validated measurement instruments are required to maximize comparability of results. Future efforts should be directed toward scaling-up evidence-based interventions to improve adolescent sexual and reproductive health in low- and middle-income countries, sustain the impacts over time, and ensure equitable outcomes.